Exploring the impact of silica and modifier ions on bioactivity and antimicrobial characteristics of quaternary 81S and ternary 85S bio-glasses - Yadav A.K.; Rath C. (My University, 2025)
Here, we assess the effect of silica and modifier ions on the biological performance of quaternary 81S bio-glass (81SiO2–16CaO–2P2O5–1Na2O mol%) against ternary 85S bio-glass (85SiO2–10CaO–5P2O5 mol%) synthesized via Stober’s method. The in vitro simulated body fluid (SBF) assay confirms the deposition of a hydroxyapatite layer on 81S and 85S bio-glasses, verified by XRD, FTIR and HRSEM analyses. However, a notable difference emerges in the pH study, where a slower degradation rate has been observed in the case of 85S compared to that of 81S bio-glass, which can be attributed to the presence of high silica content. In the MTT assay, 81S bio-glass exhibits significantly higher cell viability of 130%, surpassing that of 85S bio-glass, where 114% of cell viability is detected. While both bio-glasses exhibit antibacterial properties, 81S shows a higher efficacy in inhibiting the growth of E. coli by 47% and S. aureus by 51%, whereas 85S demonstrates comparatively lower inhibition, restraining E. coli by 16% and S. aureus by 35%. The substantial difference in antibacterial activity can be attributed to a slower dissolution rate of 85S bio-glass, which results in a very small change in pH of the surrounding environment. In conclusion, 81S bio-glass demonstrates superior bioactivity, cell proliferation and antimicrobial efficacy, making it a promising candidate for biomedical applications. © Indian Academy of Sciences 2024.